Síndrome congênita do vírus Zika: perfil sociodemográfico das mães - Freitas, Paula de Souza Silva (2019)
Objective. Describe the sociodemographic profile of mothers of children with congenital Zika syndrome. Method. This is a descriptive, cross-sectional, quantitative study. The 39 mothers of live born babies among the cases notified in 2015 and 2016 with confirmed diagnosis of congenital Zika syndrome in the state of Espírito Santo, Brazil, were invited to participate. Of these, 25 mothers were enrolled. Data were collected using a socioeconomic questionnaire and a field diary. Results. Skin color was self-reported as non-white by 19/25 mothers (74.0%), and 16 (64.0%) reported having a partner. Regarding schooling, 12 (48.0%) had completed high school. Per capita income varied from no income to US$ 1 111.11, and ranged from none to US$ 61.72 for 12 women (48.0%). Seventeen women (68.0%) lived in underprivileged periphery areas with poor living conditions. Of the 25 women, 16 (64.0%) had a job prior to the pregnancy; and of these, 12 (75.0%) were fired or quit after the baby was born. Conclusions. The profile of mothers shows that the Zika epidemics was not equanimous and preferentially affected women with low income and lower social class. In this sense, we believe that congenital Zika syndrome may be determined by social inequalities in Brazil. The data described in the present study may be useful for the planning of effective actions to ensure a social protection network for children with congenital Zika syndrome and their families